Sufi Non-Doing Offender Rehabilitation: Positive and Peacemaking Criminology in Practice - Amitay, Gila (International journal of offender therapy and comparative criminology, 2021)
Offender rehabilitation is a challenging goal that calls for ongoing creative innovations. Amongst is a non-doing rehabilitative initiation that is inspired by spiritual traditions. The aim of this paper is to present an application of non-doing offender rehabilitation that has no declared intention to rehabilitate, carried by a peacemaking Islamic Sufi route. Based on the positive criminology approach, we conducted a qualitative phenomenological study consisted of interviews with 11 ex-prisoners who were employed in the Shadhiliyya-Yashrutiyya Sufi order as construction workers and also with 35 Sufi disciple and leaders. We identified five themes of non-doing: (1) atmosphere; (2) modeling; (3) social inclusion and suspension of judgement; (4) spiritual meaning; (5) feasibility of transformative processes. The discussion presents principles of a model of non-doing rehabilitation in a spiritual community and emphasizes the research innovation in presenting non-doing as a holistic method of inclusion within a transformative faith community.